2020
DOI: 10.1101/2020.05.11.078915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recognition memory via repetition suppression in mouse hippocampal dorsal CA2 pyramidal neurons expressing the vasopressin 1b receptor

Abstract: Recognition memory, often compromised in psychiatric disorders, is a major component of declarative memory, which permits the realization that an event, object or social subject has been previously encountered. The CA2 region of the dorsal hippocampus (dCA2) is involved in social memory and responds to novel objects, in time and space. However, it remains unclear how these neurons encode either social or inanimate object recognition.Here, we show that in dCA2, encoding of social recognition memory entails supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Second, dCA2 activity is required for social novelty recognition (SNR) memory, the ability of a mouse to discriminate a novel from familiar conspecific 2,4 . And third, both electrophysiological 24,25 and cellular calcium imaging 26 studies have demonstrated that dCA2 neural activity discriminates a novel and familiar conspecific, with a higher rate of spike firing around a novel compared to familiar conspecific 24,34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, dCA2 activity is required for social novelty recognition (SNR) memory, the ability of a mouse to discriminate a novel from familiar conspecific 2,4 . And third, both electrophysiological 24,25 and cellular calcium imaging 26 studies have demonstrated that dCA2 neural activity discriminates a novel and familiar conspecific, with a higher rate of spike firing around a novel compared to familiar conspecific 24,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Two potential mechanisms may account for how dCA2 activity in response to a novel animal may promote aggression. First, enhanced firing observed in dCA2 pyramidal neurons in the presence of a novel animal 24,34 may lead to increased output to the dLS, subsequently leading to greater disinhibition of VMHvl, thus triggering aggression. The second mechanism is based on results showing that a linear classifier can provide a generalized or abstract readout of novelty versus familiarity from the population level activity of dCA2 neurons 26 .…”
Section: Discussionmentioning
confidence: 99%
“…We focused on dCA2 because of its prominent role in the encoding, consolidation, and recall of social memory 4,5,7 . Previous studies using in vivo recordings found that dCA2 neurons respond during social interactions 10,11,23 and can distinguish between a novel and a familiar animal 10 . At the same time, CA2 neurons have been found to act as place cells, firing in particular regions of an environment either in the absence or presence of a conspecific, although CA2 place fields are less precise and stable than those of its CA1 and CA3 neighbors 9,10,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The pyramidal neurons in CA2 co-express the vasopressin (Avp) 1b and oxytocin (Oxt) receptors (Avpr1b and Oxtr, respectively), through which the important neuropeptides, Avp and Oxt , carry their modulatory action on social cognition and social behavior [5][6][7] . Previously, we showed that loss of the Avpr1b from the pyramidal neurons of the CA2 results in inability of mice to recognize a familiar conspecific [6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The pyramidal neurons in CA2 co-express the vasopressin (Avp) 1b and oxytocin (Oxt) receptors (Avpr1b and Oxtr, respectively), through which the important neuropeptides, Avp and Oxt , carry their modulatory action on social cognition and social behavior [5][6][7] . Previously, we showed that loss of the Avpr1b from the pyramidal neurons of the CA2 results in inability of mice to recognize a familiar conspecific [6][7] . We also described an enhancement of social recognition following activation of the paraventricular nucleus (PVN) terminals in CA2, mediated by the Avpr1b 2 and, further, we were able to induce atypical partner preference behavior in mice through similar activation of the same neuronal pathway 8 .…”
Section: Introductionmentioning
confidence: 99%